High-fidelity simulation-based education in pre-registration healthcare programmes: a systematic review of reviews to inform collaborative and interprofessional best practice. Issue 4 (4th July 2021) - Astbury, Jayne; Ferguson, Jane; Silverthorne, Jennifer; Willis, Sarah; Schafheutle, Ellen
ABSTRACT: Simulation-based education (SBE) is recognized as an effective interprofessional teaching and learning method. Whilst there is a large volume of research evidence concerning elements of SBE there is a lack of clarity concerning foundational principles of best practice. This is important for educators wishing to utilize high-quality SBE to deliver interprofessional education. The aim of this review is to synthesize review evidence of SBE best practice in a broad range of pre-registration healthcare programs and contextualize findings in light of relevant educational theory. A systematic search of PubMed, Scopus, Medline/Ovid, British Nursing Index, and the Cochrane Library databases was undertaken in February 2020. Data extraction and quality evaluation were undertaken by two authors. Fifteen reviews were included. In addition to identifying barriers and enablers to implementation, three interdependent themes regarding SBE best practice were found: curriculum level integration and planning (curriculum level integration, the opportunity for deliberate repeated practice, distribution, and sequencing); simulation design and delivery (clearly defined learning outcomes and benchmarks, pre-brief, multiple learning strategies, interactivity and individualized learning, feedback, and debrief); and resources (facilitator competency, controlled environments). These themes broadly align with the social constructivist theory of experiential learning whereby structured opportunities to learn via concrete experience, reflective observation, abstract conceptualization, and active experimentation are provided through effective planning, design, and delivery of SBE. Interdependencies suggest that integration of SBE at curriculum-level enables planning and implementation of best practice principles which are associated with effective learning, which also inform and facilitate the availability of adequate simulation resources.